Transient Acquisition of Pluripotency During Somatic Cell Transdifferentiation with iPSC Reprogramming Factors - Maza, Itay (Nat Biotechnol, 2015)
Somatic cells can be transdifferentiated to other cell types without passing through a pluripotent state by ectopic expression of appropriate transcription factors(1,2). Recent reports have proposed an alternative transdifferentiation method in which fibroblasts are directly converted to various mature somatic cell types by brief expression of the induced pluripotent stem cell (iPSC) reprogramming factors Oct4, Sox2, Klf4 and c-Myc (OSKM) followed by cell expansion in media that promote lineage differentiation(3–6). Here we test this method using genetic lineage tracing for expression of endogenous Nanog and Oct4 and for X chromosome reactivation, as these events mark acquisition of pluripotency. We show that the vast majority of reprogrammed cardiomyocytes or neural stem cells obtained from mouse fibroblasts by OSKM-induced transdifferentiation pass through a transient pluripotent state, and that their derivation is molecularly coupled to iPSC formation mechanisms. Our findings underscore the importance of defining trajectories during cell reprogramming by different methods.